Sculpture of Panchayan Deities of National Museum: An Illustrative Stone Work of Nepal - Dulal, Lok Nath (International Journal of Culture and History, 2024)
Historical evidence proves the history of sculpturing art is as old as the history of human beings. The findings of stone sculpture and other forms of art from the different prehistoric sites of Europe, Africa and Asia have strongly supported the above mentioned acquaintance. It means the tradition of sculpturing stone art has evolved from the pre- historic culture in the world. Likewise, the tradition of creating stone sculpture and other forms of stone art also existed from the pre- historic age in Nepalese society. It is justified through the findings of hand axes and other different art objects which are being displayed in the National Museum. There are some noteworthy illustrations of Nepalese stone art in different museums abroad and in Nepal as well. Out of Nepalese stone sculptures, Panchayan deities of the national museum are considered an important specimen through religious, cultural, style, skill and technological perspectives. In this stone panel the figures of Shiva, Vishnu, Surya, Ganesh and goddess have been depicted. In Nepal, there are plenty of sculptures and paintings of these gods and goddess in single and with their families as well. But such a sculpture of this kind which has been exhibited in the stone work section of the national museum is very rare. Therefore, it is claimed that the panel is one of the important sculptures of Panchayan gods of Nepal. In this article, regarding the different issues of such sculptures going to be examined.